ЭРКИН КУРАШ, ХОТИН - ҚИЗЛАР МИСОЛИДА СПОРТ КУРАШИ ЧОҒИДАГИ ҲАРАКАТЛАРНИ ТАҲЛИЛ ҚИЛИШ - Хайдаров, Р. (SCIENCE and SOCIETY, 2017)
In article it is about a type of wrestling in the analysis the movement on the example of free-style wrestling. The attacking movements of women and girls are analyzed where the various movements of the attack are considered. A main goal of article is consideration of separate technical tactics.
Keywords: fight; the fighter; technology of national fight; technical skill; kinds of the attack; the doubled forces; fight in orchestra seats